مستوى الضغوط النفسية لدى عينة من النفسانين العيادييين الممارسين في العيادات الاستشفائية و المراكز البيداغوجية - بن خويلد بختة; بوضلعة خديجة; عاجب بومدين (My University, 2023)
The current study aims to identify the sources of occupational psychological stress facing psychologists and link them to the variables ( social status and professional experience ) . The study included a theoretical and an applied side ، and the descriptive approach was adopted in this study. To test the validity of the hypotheses ، we applied the levstein stress perception test in 1993 . And after verifying the psychometric characteristics of the study tools on an exploratory sample estimated at (20) psychologists ، it was applied to the basic study sample estimated at (31) psychologists in hospital clinics ، for both males and females . Statistical program was also used . " Spss" The study concluded that the level of psychological stress among psychologists is acceptable ، and there are statistically significant differences in the leval of psychological stress due to social status and seniority variable.